Related to testes-specific, vespid and pathogenesis protein-1 is regulated by methylation in glioblastoma - JACOBY, ELAD (D.A. Spandidos, 2014)
Related to testes-specific, vespid and pathogenesis protein-1 (RTVP-1), also known as glioma pathogenesis-related protein 1, is highly expressed and has oncogenic features in glioblastoma (GBM; World Health Organization class IV). Promoter methylation has been found to control RTVP-1 expression in prostate carcinoma, Wilms’ tumor, acute myeloid leukemia and melanoma. In this bi-institutional study, the methylation status of RTVP-1 in astrocytic brain malignancies (GBM and oligodendroglioma) was examined. The RTVP-1 promoter was hypomethylated in GBM compared with non-tumor brain samples, but was hypermethylated in oligodendroglioma. RTVP-1 methylation correlated with RTVP-1 expression at the mRNA level. In GBM, hypermethylation of the RTVP-1 promoter was associated with improved overall survival although with no statistical significance.